2009
DOI: 10.1007/s00405-009-1025-5
|View full text |Cite
|
Sign up to set email alerts
|

Topographical correlations of lateral medullary infarction with caloric- and vestibular-evoked myogenic potential results

Abstract: This study investigated the correlation of caloric- and vestibular-evoked myogenic potential (VEMP) results with topographical lesions of lateral medullary infarction. Five patients with lateral medullary infarction were enrolled in this study. Each patient underwent a battery of tests, including audiometry, caloric test, VEMP test, and magnetic resonance imaging (MRI) study. Gaze nystagmus was observed in four patients (80%), while abnormal pursuit, saccade, and optokinetic nystagmus tests were noted in all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…In contrast to the cVEMPs, caloric tests evaluate the ascending horizontal VOR originating from the horizontal semicircular canal [20]. Therefore, in LMI, topographical correlations could be made that caloric paresis is more likely linked to rostrally located infarctions while absent or delayed cVEMPs may indicate caudally located ones [24]. The contralesional or bilateral abnormalities of cVEMPs in patients with unilateral LMI were ascribed to disruption of commissural modulation between the vestibular nuclei [23].…”
Section: Lateral Medullary Infarction (Wallenberg Syndrome)mentioning
confidence: 97%
“…In contrast to the cVEMPs, caloric tests evaluate the ascending horizontal VOR originating from the horizontal semicircular canal [20]. Therefore, in LMI, topographical correlations could be made that caloric paresis is more likely linked to rostrally located infarctions while absent or delayed cVEMPs may indicate caudally located ones [24]. The contralesional or bilateral abnormalities of cVEMPs in patients with unilateral LMI were ascribed to disruption of commissural modulation between the vestibular nuclei [23].…”
Section: Lateral Medullary Infarction (Wallenberg Syndrome)mentioning
confidence: 97%
“…Topographical study of PICA territory infarction revealed that absent or delayed cVEMPs relate to caudally located infarction, while caloric areflexia may be linked with rostrally located infarction [19]. However, the cVEMP and caloric tests have various output expressions such as VEMP waveform and caloric nystagmus, which means that the results of the two tests cannot be compared.…”
Section: Discussionmentioning
confidence: 98%
“…In a patient with cerebellar cavernoma (Patient 12), normal caloric responses with delayed cVEMPs (Fig. 1) may indicate a lower brainstem lesion (23). Visual suppression during the caloric test may help to evaluate the involvement of the cerebellum via affecting the floccular Purkinje cells of cerebellum, which, in turn, inhibit the superior and medial vestibular nuclei (24).…”
Section: Audiovestibular Function Testingmentioning
confidence: 98%